Analysis of the effectiveness of implementing differentiated learning based on David Kolb's learning theory in inclusive schools - Ani, Aulia Fitri; Lystiana, Alfina Nur; Romadhan, Aditya Dwi; Akbar, Aslam Maulana; Isma, Fadlin Ade (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
This study aims to analyze the effectiveness of the implementation of differentiated learning carried out in various inclusive schools by looking at the implementation process and obstacles experienced. The study was conducted using the systematic literature review (SLR) method. Data collection techniques were carried out by selecting relevant literature from various scientific literature ranging from 2019 to 2024. Data analysis was carried out systematically by filtering articles based on the relevance of the title and abstract, followed by an in-depth review to find relevant data. The results of the study indicate that the implementation of differentiated learning is effective in helping diverse students understand the material in a way that accommodates differences in the learning process. However, the results of the study also show the need for teacher training and improved school facilities so that the process of accommodating different learning processes becomes more effective. In addition, holistic cooperation is needed from various elements so that the implementation of differentiated learning can be carried out effectively and sustainably.